2010
DOI: 10.1029/2007wr006449
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian multiresponse calibration of TOPMODEL: Application to the Haute‐Mentue catchment, Switzerland

Abstract: [1] This paper introduces a general framework that evaluates a numerical Bayesian multiresponse calibration approach based on a Gibbs within Metropolis searching algorithm and a statistical likelihood function. The methodology has been applied with two versions of TOPMODEL on the Haute-Mentue experimental basin in Switzerland. The approach computes the following: the parameter's uncertainty, the parametric uncertainty of the output responses stemming from parameter uncertainty, and the predictive uncertainty o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
4
5
0
Order By: Relevance
“…For example, Engeland, Xu & Gottschalk (2005) showed that model structural uncertainty is larger than model parameter uncertainty for simple conceptual models with few well-defined parameters. Our results also confirm the study of Talamba, Parent & Musy (2010) for a lumped hydrological model. Talamba, Parent & Musy (2010) showed, for a fully distributed hydrological model, that accounting for input rainfall uncertainty did not lead to a substantial change in terms of estimated parameters and model performance, because other sources of uncertainty dominated the total predictive uncertainty.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…For example, Engeland, Xu & Gottschalk (2005) showed that model structural uncertainty is larger than model parameter uncertainty for simple conceptual models with few well-defined parameters. Our results also confirm the study of Talamba, Parent & Musy (2010) for a lumped hydrological model. Talamba, Parent & Musy (2010) showed, for a fully distributed hydrological model, that accounting for input rainfall uncertainty did not lead to a substantial change in terms of estimated parameters and model performance, because other sources of uncertainty dominated the total predictive uncertainty.…”
Section: Discussionsupporting
confidence: 88%
“…Our results also confirm the study of Talamba, Parent & Musy (2010) for a lumped hydrological model. Talamba, Parent & Musy (2010) showed, for a fully distributed hydrological model, that accounting for input rainfall uncertainty did not lead to a substantial change in terms of estimated parameters and model performance, because other sources of uncertainty dominated the total predictive uncertainty. This is similar to our case study, where in all three approaches the prediction intervals have a similar width and range.…”
Section: Discussionsupporting
confidence: 88%
“…For example, Engeland et al (2005) showed that model structural uncertainty is larger than model parameter uncertainty for simple conceptual models with few well-de ned parameters. We also con rm the study of Talamba et al (2010) for a lumped hydrological model. Talamba et al (2010) showed, for a fully distributed hydrological model, that accounting for input rainfall uncertainty did not lead to a substantial change in terms of estimated parameters and model performance, because other sources of uncertainty dominated the total predictive uncertainty.…”
Section: Predictionsupporting
confidence: 61%
“…We also con rm the study of Talamba et al (2010) for a lumped hydrological model. Talamba et al (2010) showed, for a fully distributed hydrological model, that accounting for input rainfall uncertainty did not lead to a substantial change in terms of estimated parameters and model performance, because other sources of uncertainty dominated the total predictive uncertainty. This is similar to our case study, where in all three approaches the prediction intervals have a similar width and range.…”
Section: Predictionsupporting
confidence: 61%
“…These efforts generally indicate relatively close agreement between informal and formal methods (Beven et al, 2008;Jeremiah et al, 2011;Jin et al, 2010;Li et al, 2010;Qian et al, 2003;Vrugt et al, 2008;Yang et al, 2008). Most of the above comparative papers only considered single-criterion calibration cases, and only a few, e.g., Balin-Talamba (2004) and Balin-Talamba et al (2010), considered multi-criteria calibration of hydrologic models.…”
Section: Introductionmentioning
confidence: 95%